A noninvasive method for the determination of in vivo mitral valve leaflet strains. (14th September 2018) - Rego, Bruno V.; Khalighi, Amir H.; Drach, Andrew; Lai, Eric K.; Pouch, Alison M.; Gorman, Robert C.; Gorman, Joseph H.; Sacks, Michael S.
Abstract: Assessment of mitral valve (MV) function is important in many diagnostic, prognostic, and surgical planning applications for treatment of MV disease. Yet, to date, there are no accepted noninvasive methods for determination of MV leaflet deformation, which is a critical metric of MV function. In this study, we present a novel, completely noninvasive computational method to estimate MV leaflet in‐plane strains from clinical‐quality real‐time three‐dimensional echocardiography (rt‐3DE) images. The images were first segmented to produce meshed medial‐surface leaflet geometries of the open and closed states. To establish material point correspondence between the two states, an image‐based morphing pipeline was implemented within a finite element (FE) modeling framework in which MV closure was simulated by pressurizing the open‐state geometry, and local corrective loads were applied to enforce the actual MV closed shape. This resulted in a complete map of local systolic leaflet membrane strains, obtained from the final FE mesh configuration. To validate the method, we utilized an extant in vitro database of fiducially labeled MVs, imaged in conditions mimicking both the healthy and diseased states. Our method estimated local anisotropic in vivo strains with less than 10% error and proved to be robust to changes in boundary conditions similar to those observed in ischemic MV disease. Next, we applied our methodology to ovine MVs imaged in vivo with rt‐3DE and compared our results to previously published findings of in vivo MV strains in the same type of animal as measured using surgically sutured fiducial marker arrays. In regions encompassed by fiducial markers, we found no significant differences in circumferential( P = 0.240) or radial ( P = 0.808) strain estimates between the marker‐based measurements and our novel noninvasive method. This method can thus be used for model validation as well as for studies of MV disease and repair. Abstract : Assessment of mitral valve (MV) function is important in many diagnostic, prognostic, and surgical planning applications for treatment of MV disease. Yet, to date, there are no accepted noninvasive methods for determination of MV leaflet deformation, which is a critical metric of MV function. In this study, we present a novel, completely noninvasive computational method to estimate MV leaflet strains from clinical‐quality real‐time three‐dimensional echocardiography (rt‐3DE) images and validate the approach using in vivo and in vitro marker‐based strain measurements.